The perception of the healthcare workers about the Hospital Infection Control Committee - an exploratory study - Adriana C. Oliveira; Sintia Evangelista; Thabata C. Lucas; Paulo H.O. Mourão; Wanessa T. Clemente (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2006)
Introduction:The actions of the Infection Hospital Control Comitte (HICC) according to federal regulations 2616/98, are based essentially on the surveillance epidemiologic that makes possible the definition of guidelines's prevention and control infection. However a high unrest for the health care workers refer the fact that during the health care they haven't understood that the infection control is an ineherent aspect in their practice because of the risk in manipulation of organic matter, secretions and excretions, in addition to contact with microorganisms disseminated by differents route of transmission.Objective: to identify the perception of the healthcare workers team about the performance of Infection Hospital Control Committee (HICC). Methods: This is a descriptive study, completed in a hospital university of Belo Horizonte. A questionnaire was applied to 86 professionals (nurses, physicians and physiotherapists). Results: It was found that 88% of the professionals had knowledge of the meaning of the acronym HICC, 64% of them could identify a case of hospital infection, however just 48,8% had knowledge about the identification criterion of the resistant microorganisms. The lack of knowledge and commitment were the main cause for the low or not adhesion of control measures for hospital infection. In relation to the professional's perception of the HICC, the majority considers it actively participative. Conclusion: this study has important contributions for the reflections of the practices of the healthcare workers team, as well as, for the HICCs think about yours strategic of the training and involvement with the hospital community.